Emergent Magnetic Phases in Pressure-Tuned van der Waals Antiferromagnet FePS_{3} - Matthew J. Coak; David M. Jarvis; Hayrullo Hamidov; Andrew R. Wildes; Joseph A. M. Paddison; Cheng Liu; Charles R. S. Haines; Ngoc T. Dang; Sergey E. Kichanov; Boris N. Savenko; Sungmin Lee; Marie Kratochvílová; et al. (Physical Review X, 2021)
Layered van der Waals 2D magnetic materials are of great interest in fundamental condensed-matter physics research, as well as for potential applications in spintronics and device physics. We present neutron powder diffraction data using new ultrahigh-pressure techniques to measure the magnetic structure of Mott-insulating 2D honeycomb antiferromagnet FePS_{3} at pressures up to 183 kbar and temperatures down to 80 K. These data are complemented by high-pressure magnetometry and reverse Monte Carlo modeling of the spin configurations. As pressure is applied, the previously measured ambient-pressure magnetic order switches from an antiferromagnetic to a ferromagnetic interplanar interaction and from 2D-like to 3D-like character. The overall antiferromagnetic structure within the ab planes, ferromagnetic chains antiferromagnetically coupled, is preserved, but the magnetic propagation vector is altered from k=(0,1,1/2) to k=(0,1,0), a halving of the magnetic unit cell size. At higher pressures, coincident with the second structural transition and the insulator-metal transition in this compound, we observe a suppression of this long-range order and emergence of a form of magnetic short-range order which survives above room temperature. Reverse Monte Carlo fitting suggests this phase to be a short-ranged version of the original ambient-pressure structure—with the Fe moment size remaining of similar magnitude and with a return to antiferromagnetic interplanar correlations. The persistence of magnetism well into the HP-II metallic state is an observation in contradiction with previous x-ray spectroscopy results which suggest a spin-crossover transition.